2015
DOI: 10.1007/s12519-015-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid intima-media thickness and carotid arterial stiffness in children with adenotonsillar hypertrophy

Abstract: The present study revealed increased carotid intima-media thickness in children with adenotonsillar hypertrophy. The risk of subclinical atherosclerosis may be higher in children with adenotonsillar hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
1
0
1
Order By: Relevance
“…Our measurements are congruent with earlier reports from 5‐ to 10‐year‐old controls, 20 , 21 who demonstrated a stiffness index (beta) of 2.9 to 3.0. Arterial stiffness reflects a smaller arterial capacity to respond to pressure changes, either as a defect fetal deposition of elastin in the arterial wall, 22 or due to accelerated loss of elasticity.…”
Section: Discussionsupporting
confidence: 92%
“…Our measurements are congruent with earlier reports from 5‐ to 10‐year‐old controls, 20 , 21 who demonstrated a stiffness index (beta) of 2.9 to 3.0. Arterial stiffness reflects a smaller arterial capacity to respond to pressure changes, either as a defect fetal deposition of elastin in the arterial wall, 22 or due to accelerated loss of elasticity.…”
Section: Discussionsupporting
confidence: 92%
“…Two pediatric studies (including a mixed child–adolescent cohort and an adolescent-only cohort) found no association between OSA and cIMT as a surrogate measure of atherosclerosis independently of obesity,328,329 but a more recent study of 40 children with adenotonsillar hypertrophy aged 5–10 years and 36 age- and BMI-matched controls found a higher cIMT in the adenotonsillar hypertrophy group 330. One study of 30 children and adolescents with primary snoring vs BMI-, age-, and sex-matched controls found a greater degree of peripheral arterial stiffness as measured by brachial–ankle PWV in those with primary snoring,329 but two subsequent studies found no association between OSA and central arterial stiffness and carotid–femoral PWV 330,331. Finally, one study of preschool-aged and school-aged children with OSA found a reduced left ventricular ejection fraction (although no clinical signs of heart failure) and that in some of the subjects, treatment of OSA improved left ventricular ejection fraction 332…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 95%
“…В недавнем исследовании [12] визуализационный показатель толщины комплекса интимамедиа (КИМ) у детей от 5 до 10 лет с ХТ оказался выше, чем в контрольной группе здоровых детей того же возраста, что дало возможность авторам говорить о повышенном риске развития субклинического атеросклероза в этом возрасте при анамнезе заболевания от 1 до 10 лет. Однако при этом обе группы значимо не различались по некоторым показателям СЖ.…”
Section: характеристика факторов риска у пациентов с декомпенсированн...unclassified